Perceptions of Mothers’ regarding the Effect of Cartoon Programs on Primary School Children - TAJ, Dr SAIRA; KALSOOM, Dr TAHIRA; NADER, Dr MOAFIA (The journal of contemporary issues in business and government, 2021)
This research study assesses whether cartoon programs, the most famous entertainment among children and elders globally, are affecting the behaviour of our children. The researchers conducted interviews, and a survey from mothers of Lahore city. By using convenient sampling technique, researchers selected 100 mothers of primary school going children who have television set with internet or cables in their homes. The survey research was conducted by utilizing a self-constructed instrument. Fifteen mothers were interviewed using a self-constructed, semi-structured interview protocol. The study design is mixed method research. The results from both methods were quite similar and consolidated. Study showed that the cartoon programs are influencing our children to a considerable extent. Especially they have a strong and negative effect on the language and verbal responses of children. In today’s scenario in which children use to watch cartoons for a great stretch of their day it was recommended that the cartoon programs should be deeply screened and should be carefully developed keeping in view the social and moral values. There should be valid laws for censor policies for national and international cartoon programs. A great responsibility is also on the shoulders of parents, especially mothers and teachers who have to play critical role in this whole process as they can help them learning something out from a negative experience too.